Indicating relationship success : finding new agricultural Business-to-Business partners by evaluating the potential for relationship success - Ektander, Vilhelm; Ryssén, Erik (SLU/Dept. of Economics, 2013)
When a company seeks to enter a new market, the multiple choices of possible new business relationships exist. Further, establishing new relationships is a time-consuming procedure associated with high uncertainty and high costs. Hence, if the firm does not succeed in pinpointing the most suitable business partners to collaborate with, the firm may both forfeit other possible good relationships, as well as resources invested. Based on this notion the aim of this thesis is to explore how a manufacturing company can base the selection of future dealership Business-to-Business partners by evaluating indicators of a possible business relationship’s potential to become successful.